2007
DOI: 10.1016/j.apgeochem.2006.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating main factors controlling aluminum solubility in acid forest soils, southern and southwestern China

Abstract: The mechanism controlling Al solubility in Chinese acidic forest soils is not clearly understood. This is the main limitation to the ability to generate adequate dose-response prediction models of the ecological effect of acid rain. To evaluate the relative significance of possible processes, soils and soil solutions from five forest catchments, located in southern and southwestern China, were collected and analyzed for chemical parameters. Monitoring showed that inorganic Al (Al i ) was the dominant fraction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…In line with earlier studies, we found a relatively small increase in Al 3+ concentration in soil water at Tieshanping with decreasing pH, in the pH range < 4. This minor increase in Al concentration with decreasing pH was not in accordance with Al(OH) 3 equilibrium reactions (Figure ) [ Mulder and Stein , ; Guo et al ., ]. The slope of the regression line was close to zero, much lower than the value of 1.65 for forests in North America [ Reuss et al ., ].…”
Section: Discussionmentioning
confidence: 77%
“…In line with earlier studies, we found a relatively small increase in Al 3+ concentration in soil water at Tieshanping with decreasing pH, in the pH range < 4. This minor increase in Al concentration with decreasing pH was not in accordance with Al(OH) 3 equilibrium reactions (Figure ) [ Mulder and Stein , ; Guo et al ., ]. The slope of the regression line was close to zero, much lower than the value of 1.65 for forests in North America [ Reuss et al ., ].…”
Section: Discussionmentioning
confidence: 77%
“…The mean mineral soil depth is between 40 and 80 cm, and the soil was rather homogeneous [33] , [34] . This acidic soil is representative for Chongqing and characterized by low levels of exchangeable Ca and high levels of exchangeable Al [33] , [35] , [41] . In the last decades the Masson pine forest ecosystem has declined due to severe soil acidification [33] , [35] .…”
Section: Study Sites and Methodsmentioning
confidence: 99%
“…parts of China where pH value of rain water is lower than 4.5 and sulfur deposition exceeds the critical load, and the acid rain problem has been addressed by the national authorities [39] . The soil of Masson pine forests in Chongqing is generally acidic, with low amounts of exchangeable Ca and high amounts of exchangeable Al [33] , [35] , [40] , [41] . Masson pine is highly sensitive to Al [42] .…”
Section: Introductionmentioning
confidence: 99%
“…Garcia-Rodeja1997; Guo et al, 2007;Van Hees et al, 2001) who found that the mobility of Al, as well as of other chemical elements including Ni, Zn, Mn, was enhanced by increasing the acidity of the soils where the type of soils determined which elements becomes mobile. The source for the acidity of the groundwater upstream of the DLV is probably a combination of acid rain, the production of H + during redox reactions caused by initial exposure of organic layers during lowering of the water table (Eq.…”
Section: Chemistry and Field Parameters Of Ground-and Surface Watermentioning
confidence: 98%